2012
DOI: 10.2967/jnumed.112.109413
|View full text |Cite
|
Sign up to set email alerts
|

PET of Glucagonlike Peptide Receptor Upregulation After Myocardial Ischemia or Reperfusion Injury

Abstract: Glucagonlike peptide (GLP-1) and its receptor (GLP-1R) exhibit cardioprotective effects after myocardial ischemia and reperfusion (MI/R) in both animal studies and clinical trials. However, the kinetics of GLP-1R expression in the infarcted/ischemic myocardium has not yet been explored. The purpose of this study was to monitor the presence and time course of regional myocardial GLP-1R expression after MI/R with noninvasive PET. Methods: Male Sprague-Dawley rats underwent a 45-min transient left coronary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…I/R can cause additional cell death and increased infarct size, which is called I/R injury [26]. Studies have proven that lncRNA and GLP-1R are essential in myocardial I/R injury [27,28]. Therefore, our study aimed to determine the effect of lncRNA LINC00652 on myocardial I/R injury in mice with sevoflurane treatment by targeting GLP-1R through the cAMP/PKA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I/R can cause additional cell death and increased infarct size, which is called I/R injury [26]. Studies have proven that lncRNA and GLP-1R are essential in myocardial I/R injury [27,28]. Therefore, our study aimed to determine the effect of lncRNA LINC00652 on myocardial I/R injury in mice with sevoflurane treatment by targeting GLP-1R through the cAMP/PKA signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the Sevo + I/R group, the LINC00652 expression in the myocardium of the si-LINC00652 + Sevo + I/R group further decreased, the expression of the GLP-1R and CREB proteins further increased, the infarct size further reduced, the number of apoptotic myocardial cells and inflammatory factors IL-1ÎČ and TNF-α in serum significantly decreased. A previous study showed that GLP-1 and its receptor GLP-1R exhibited cardio-protective effects after myocardial I/R in animal studies and clinical trials [28]. Several lncRNAs are dysregulated during acute myocardial infarction or heart failure, whereas others could control hypertrophy, mitochondrial function and cardiomyocyte apoptosis, and identified cardiovascular lncRNAs might play significant roles in cardiovascular diseases [36].…”
Section: Discussionmentioning
confidence: 99%
“…48Y53 In fact, early evidence suggests that glucagon-like peptide-1 receptor expression is upregulated in the heart in response to ischemia. 54 The cardioprotective and vasculoprotective effects of glucagon-like peptide-1 appear to be partially independent of the known glucagon-like peptide-1 receptor because neither pharmacologic blockade of the glucagonlike peptide-1 receptor signaling pathway 55 nor knockout of the glucagon-like peptide-1 receptor in mice 55 completely abolishes all of the observed effects.…”
Section: Effects Of Glucagon-like Peptide-1 and Glucagon-like Peptidementioning
confidence: 96%
“…30 A study in rats shows regulation of the GLP-1 receptor in the heart within a few hours of experimental ischemia, that persisted for up to 3 days. 31 Sokos et al investigated the efficacy of a 5-week continuous infusion of GLP-1, in addition to standard therapy, in 12 patients with New York Heart Association class 3 and class 4 heart failure, when compared with nine control subjects. It Protective against ischaemic damage.…”
Section: Effects Of Glp-1 On the Heartmentioning
confidence: 99%